Ex post evaluation of developmental interventions in large scale infrastructure projects: The case of Vistonida rural area - E., Stathakis; E., Stambologlou; Manoliadis, O. (International Journal of Scientific Research and Management (IJSRM), 2020)
The structural development interventions carried out by the European Union (EU) aim to accelerate the real convergence of 28 Member States, mainly those lagging behind interventions. Most of these contribute to better environmental protection,  better life condition for farmers and flood protection. Evaluation of infrastructure projects contributing to spatial growth in ex-ante, ongoing, and ex-post basis is an essential activity to answer several issues raised during the growth mentioned above process. This paper aims to evaluate on ex-post basis integrated developmental interventions-large scale infrastructure projects in rural areas, using a combined method based on Social Cost-Benefit Analysis (SCBA), sustainable and rural growth indicators coming from official organizations along with the n-Dimensional (nD) modelling. The studied developmental interventions refer to Vistonida's rural area, an area to which large-scale infrastructure financed and carried out by the Greek state. They contributed to the modernization and adaptation of the agriculture sector, improving its qualitative and quantitative performance. The needed data derived from the Hellenic National Statistical Services, Ministry of Agriculture, Greek Payment Authority of Common Agricultural Policy (C.A.P.) and concern a period of forty years and they are referred to Land redistribution, irrigation land, crops structure. According to this study, the large-scale agriculture infrastructure contributes significantly to the improvement of the growth rates of a rural spatial productive system as a whole. The application of the combined method was simple, easily understood by policymakers, adequately reliable, and precise.